A prospective study of mortality from cryptococcal meningitis following treatment induction with 1200 mg oral fluconazole in Blantyre, Malawi. - Katherine M Gaskell; Camilla Rothe; Roshina Gnanadurai; Patrick Goodson; Chikondi Jassi; Robert S Heyderman; Theresa J Allain; Thomas S Harrison; David G Lalloo; Derek J Sloan; Nicholas A Feasey (PLoS ONE)
Objective We have previously reported high ten-week mortality from cryptococcal meningitis in Malawian adults following treatment-induction with 800 mg oral fluconazole (57% [33/58]). National guidelines in Malawi and other African countries now advocate an increased induction dose of 1200 mg. We assessed whether this has improved outcomes. Design This was a prospective observational study of HIV-infected adults with cryptococcal meningitis confirmed by diagnostic lumbar puncture. Treatment was with fluconazole 1200 mg/day for two weeks then 400mg/day for 8 weeks. Mortality within the first 10 weeks was the study end-point, and current results were compared with data from our prior patient cohort who started on fluconazole 800 mg/day. Results 47 participants received fluconazole monotherapy. Despite a treatment-induction dose of 1200 mg, ten-week mortality remained 55% (26/47). This was no better than our previous study (Hazard Ratio [HR] of death on 1200 mg vs. 800 mg fluconazole: 1.29 (95% CI: 0.77-2.16, p = 0.332)). There was some evidence for improved survival in patients who had repeat lumbar punctures during early therapy to lower intracranial pressure (HR: 0.27 [95% CI: 0.07-1.03, p = 0.055]). Conclusion There remains an urgent need to identify more effective, affordable and deliverable regimens for cryptococcal meningitis.